Peningkatan Kualitas Jasa Pewarnaan Produk Celana Jeans dengan Penerapan Six Sigma & Eksperimen Taguchi Attribute Characteristic (Kasus CV. Ciharuman Laundry) - Rida Norina; Insan Fauzi (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2021)
CV. Ciharuman Laundry is a pants dyeing services industry. Companyâ€™s production process often defect produce. The consequences of the action defect product will have an impact on increasing production costs. One of dominant defect is not equal coloring for about 19,8%. The method used to reduce the percentage of defects is the six sigma concept (DMAIC). To find out the cause of the defect is analysis by using a casual diagram and FMEA conclusion the dominant cause is not right a compare coloring agent, water and temperature on the washing process, so improvements needed to the process with implementation of experiment Taguchi. Implementation stage of experiment divided into 3, that is first experiment which is actual condition of company right now, second experiment was done using Taguchi settings on an orthogonal array L8(27), and third experiment which was the result of confirmation experiment. The result of experiment obtained optimal settings for do the washing process temperature is 100Â°C, dose of the drug is 8 kilograms and the water ratio is 400 liters. The confirmation result of 120 sample by 24 attempts optimal settings proved to be able to reduce percentage of defect by 79%.